METODE PELAKSANAAN PEKERJAAN OVERBRIDGE BENTANG 30M - INDRA KRISNA SUKMA RAHAYU; YAYAT HENDRAYANA (Universitas Majalengka, 2021)
The method of implementing the Overbridge / bridge determines the stages that must be carried out in the Overbridge work, this study aims to analyze the work of making the Overbridge, especially in bored pile, pile cap, abutment, and girder work. The methodology used in this research is to directly see and observe Overbridge work, the Overbridge project location is located in Kertajati District, Cipali-Palimanan Toll Access to West Java International Airport, Majalengka, the concrete used is callas concrete B, F'c 20 90.130) with Slump value is 16 + - 2cm and for ironwork uses 32 mm main iron and 16 mm spiral. Then for the tools used are drilling machines, 45 ton capacity cranes, 6 m3 mixer truck, dum trucks and vibrators.